Literatur Review: Peran Penting Audit Investigatif Professional Judgment, dan Whistleblower Terhadap Pengungkapan Fraud - Adelia Putri; Thresia Agnes Monica Simarmata; Mayang Murni (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This study aims to evaluate the impact of three main factors, namely Investigative Audit, Professional Judgment, and Whistleblower on the level of disclosure of fraud cases at the Audit Board of the Republic of Indonesia, taking into account accounting and audit practices. The existence of fraud in a company's financial statements has a serious impact on the integrity of financial markets and investor confidence. Therefore, this study adopts a comprehensive approach to identify the factors that influence the likelihood of fraud disclosure. This research method involves an in-depth literature review to understand the concept and impact of Investigative Audit, Professional Judgment, and Whistleblower on fraud disclosure. The results of this study will provide better insight into the contribution of these factors to fraud disclosure. The practical implications of this research include increased understanding of the importance of implementing Investigative Audits in detecting and preventing fraud. In addition, this research is also expected to increase the role of Professional Judgment in the audit process, as well as strengthen the role of Whistleblowers as a valuable source of information in revealing fraudulent acts.